White starburst-like pattern as a dermoscopic clue in Old World cutaneous leishmaniasis - Pablo Fernandez-Crehuet; Ricardo Ruiz-Villaverde (Sociedade Brasileira de Dermatologia, 2017)
Abstract: A 70-year-old woman was referred to our dermatological unit by her general practitioner last summer, with a history of a two-month ulcerated purplish lesion on her left arm that spread centrifugally and that unsuccessfully treated with topical corticosteroids. The dermoscopic evaluation revealed an erythematous macula with central ulceration that showed the characteristic called "white starburst-like pattern" and some vascular structures (dotted vessels, polymorphous⁄ atypical vessels). The diagnosis of cutaneous leishmaniasis was made after histopathologic analysis and polymerase chain reaction essay.